RELIGIOUS AUTHORITY IN VIRTUAL SPACE: SHIFTING LEGITIMACY OF ULAMA IN THE NEW MEDIA ECOSYSTEM - Harahap, Mhd. Harvinsyah Rozi; Rubino, Rubino; Tanjung, Ahmad Sujai (Program Pascasarjana UIN Sumatera Utara, 2026)
The development of the new media ecosystem has significantly transformed the production and recognition patterns of religious authority in Indonesia. Amidst the increasingly massive penetration of the internet and social media, the legitimacy of ulama (Islamic scholars) no longer rests solely on institutional credentials, scholarly chains of narration, and recognition from traditional communities, but is also shaped by digital visibility, communication performativity, and the logic of platform algorithms. This article aims to systematically analyze the shift in ulama legitimacy in the virtual space by exploring the relationship between platform structures, communication strategies of religious figures, and audience participation in constructing or delegitimizing authority. The research uses a qualitative approach with a digital case study and digital ethnography design. Data were collected through observations of da'wah content on YouTube, Instagram, and TikTok, documentation of public interactions, and semi-structured interviews with religious figures and active followers. The analysis was conducted using thematic analysis with triangulation of sources and methods to ensure the credibility of the findings. The results indicate three main models of legitimacy: institutional-traditional, performative-digital, and hybrid, with the hybrid model proving more adaptive and stable in a networked society. Platform algorithms and audience participation play significant roles in shaping visibility and negotiating legitimacy. This study concludes that the shift in the legitimacy of ulama (ulama) is not the elimination of traditional authority, but rather a reconfiguration of social recognition mechanisms within the digital ecosystem. This implication underscores the importance of integrating scientific integrity and strategic digital literacy, and opens up opportunities for further research based on mixed-method approaches and social network analysis.